10th International Conference on Nuclear Engineering, Volume 1 2002
DOI: 10.1115/icone10-22506
|View full text |Cite
|
Sign up to set email alerts
|

Application of Seismic Isolation to the STAR-LM Reactor

Abstract: This paper presents findings from our initial work in developing a seismic isolation system for the STAR-LM reactor design. Research and development was carried out to determine the characteristics of the isolator device. The heavy weight and small footprint presented a challenge in bearing design and bearing placement. Results are also presented from a study on the use of three-dimensional seismic isolation devices to the full-scale reactor. Both two-dimensional (i.e., one device for horizontal isolation only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…An analysis has been carried out to determine the required number and type of isolators. 12 It was concluded that seven pairs of threedimensional isolators provide sufficient isolation.…”
mentioning
confidence: 99%
“…An analysis has been carried out to determine the required number and type of isolators. 12 It was concluded that seven pairs of threedimensional isolators provide sufficient isolation.…”
mentioning
confidence: 99%